Appraisal of instructional and leadership roles of teachers in achieving sustainable education for students with learning disabilities in Ibadan, Nigeria (2020)
This study investigated the extent to which teachers perform the roles of instruction and leadership towards achieving sustainable education for students with learning disabilities in regular education classrooms. The descriptive research design was adopted. The sample size for the study is 143 regular and special education teachers comprising 61 males and 82 females. A self-designed questionnaire titled “Instructional and Leadership roles of Teachers Scale (r= 0.75) was used for data collection. Data were analysed using descriptive statistics of frequency distributions, percentage analysis, mean and Pearson Product Moment Correlation at 0.05 level of significance. The results showed that to a large extent, majority of the participants (93.7%, n=T34) (weighted mean =2.83 with criterion mean as > 2.50) agreed that they perform instructional roles (collaboration, differentiation of instruction, provide accommodations and individualized instruction) towards achieving sustainable education for students with learning disabilities in the regular education classrooms. It was also revealed that majority of the participants (93.7%, n=134) (weighted mean =2.87 with criterion mean as > 2.50) agreed that they perform leadership roles (such as serve as mentors to new colleagues, model a willingness to take risks and facilitate the scheduling and delivery of related services) towards achieving sustainable education for students with learning disabilities in the regular education classrooms. The result also showed that there is a significant relationship between how teachers perform instructional roles and how they perform their leadership roles as ways of achieving sustainable education for students with learning disabilities (r = 0.499, n= 143, p(0.000)<.05). Among others, the researcher recommends that more teacher commitment is required to enhance effective delivery of instructional and leadership roles by teachers in regular education school settings. Also, there should be adequate planning and implementation of individualized instruction for students with learning disabilities by special and regular education teachers.